Core density turbulence in the HSX Stellarator. (23rd October 2015) - Deng, C.B.; Brower, D.L.; Anderson, D.T.; Anderson, F.S.B.; Briesemeister, A.; Likin, K.M.
Abstract: Broadband turbulent density fluctuations are explored in the helically symmetric stellarator experiment (HSX) by investigating changes related to plasma heating power and location. No fluctuation response is observed to occur with large changes in electron temperature and its gradient, thereby eliminating temperature gradient as a driving mechanism. Instead, measurements reveal that density turbulence varies inversely with electron density scale length. This response is consistent with density gradient drive as one might expect for trapped electron mode (TEM) turbulence. In general, the plasma stored energy and particle confinement are higher for discharges with reduced fluctuations in the plasma core. When the density fluctuation amplitude is reduced, increased plasma rotation is also evident suggesting a role is being played by intrinsic plasma flow.